Pengaruh Pijat Oksitosin Terhadap Involusi Uteri pada Ibu Nifas di Tpmb R Kabupaten Purwakartatahun 2024 - Oktaviany, Dyan; Ismaryani, Fitria (CV. Green Publisher Indonesia, 2025)
Maternal death is the death of a mother during pregnancy or within 42 days after the end of pregnancy. The highest cause of maternal death was due to bleeding (31%). The mother's condition after childbirth changes (uterine involution). Efforts to maintain uterine contractions through oxytocin massage. The effect of oxytocin massage on uterine involution of postpartum mothers is known at TPMB R, Purwakarta Regency in 2024. The target of this study is physiological postpartum mothers. The type of research used is a quasi-experimental experiment by conducting a pre and posttest approach of two group design. The research subjects were divided into two groups, namely the intervention group and the control group. The sample in this study was taken as a total of 36 people consisting of 18 people as the control group respondents and 18 people as the treatment group. The results of univariate analysis to explain the research variables, bivariate analysis to explain the influence, hypothesis testing of the Chi-square statistical test using the SPSS program with a significance limit of 0.05 so that the P value is 0.05. The control group and the treatment group had a Pvalue value of 0.007 (0.05), there was a difference between the control group and the treatment of the uterine involution process, the age confounding variable had a Pvalue value of 0.017 ɑ (0.05), there was an influence of the age group on uterine involution in postpartum mothers. The parity confounding variable is Pvalue 0.026 ɑ (0.05), there is an effect of the parity group on uterine involution in postpartum mothers. It can be used as a source of reference and evaluation in providing care for postpartum mothers by providing oxytocin massage.